Reactivity of Cyanide at Water-Ice Interfaces: Implications for the Search for Organics on Icy Worlds - Marín-Yaseli, Margarita R.; González-Toril, Elena; Ruiz-Bermejo, Marta (Frontiers in Astronomy and Space Sciences, 2020)
Icy moons in our solar system are targets of interest to search for signs of life and habitability beyond Earth. They are the astrobiological aim for several developing space missions (JUICE, Europa Clipper and Europa Lander). A further understanding of the processes that force a planetary object to develop a biological system and to develop habitability conditions could be obtained by adopting a prebiotic chemistry point of view. In this regard, it is highly interesting to search for organic compounds synthesized from cyanide since it has been proposed that polymerization of NH4CN would be applicable to icy planetary environments. Thus, the effect of water freeze-thaw cycles, UV-radiation and salts on the polymerization of NH4CN was explored as an approach to understand the likely rich organic chemistry of icy worlds. As a result, insoluble and soluble NH4CN polymers, synthesized under multiple conditions, were analyzed by GC-MS. A diverse set of amino acids, carboxylic acids and several N-heterocycles were identified. Glyoxylic acid was detected under particular reaction conditions, extending the plausible favorable conditions for the emergence of this molecule, referred to as the “glyoxylate scenario”. In addition, the GC-MS results were studied by multivariate analysis, showing that the ice-water interfaces may be ideal places to develop complex organic chemistry from a carbon source as simple as cyanide.